Literasi Investasi Syariah, Religiusitas, dan Profil Risiko dalam Membentuk Keputusan Investasi pada Platform Bibit: Peran Moderasi Gender - Zida Naela Salsabilla; Sita Deliyana Firmialy (Society, 2025)
This study investigates the impact of Sharia investment literacy, religiosity, and risk profile on investment decision-making among users of the Bibit platform, with gender serving as a moderating variable. Although financial technology usage has surged among Millennials and Generation Z, participation in Sharia-compliant investments remains relatively low. This gap may be attributed to limited Sharia investment literacy, varying degrees of religiosity, and diverse individual risk profiles. Using a quantitative approach, data were collected from 221 Muslim investors on the Bibit platform via an online survey and analyzed using Structural Equation Modeling (SEM). The results indicate that both Sharia investment literacy and religiosity significantly and positively influence investment decisions, whereas risk profile shows no significant effect. Additionally, gender moderates the relationship between religiosity and investment decisions, but does not moderate the effects of Sharia investment literacy or risk profile. These findings offer valuable insights for financial platform developers and policymakers seeking to enhance Sharia investment engagement through targeted literacy programs and inclusive, gender-sensitive strategies for younger demographics.